CAR-T cell therapy for hematological malignancies: Limitations and optimization strategies - Huang, Jiawen; Huang, Xiaobing; Huang, Juan (Frontiers in Immunology, 2022)
In the past decade, the emergence of chimeric antigen receptor (CAR) T-cell therapy has led to a cellular immunotherapy revolution against various cancers. Although CAR-T cell therapies have demonstrated remarkable efficacy for patients with certain B cell driven hematological malignancies, further studies are required to broaden the use of CAR-T cell therapy against other hematological malignancies. Moreover, treatment failure still occurs for a significant proportion of patients. CAR antigen loss on cancer cells is one of the most common reasons for cancer relapse. Additionally, immune evasion can arise due to the hostile immunosuppressive tumor microenvironment and the impaired CAR-T cells in vivo persistence. Other than direct antitumor activity, the adverse effects associated with CAR-T cell therapy are another major concern during treatment. As a newly emerged treatment approach, numerous novel preclinical studies have proposed different strategies to enhance the efficacy and attenuate CAR-T cell associated toxicity in recent years. The major obstacles that impede promising outcomes for patients with hematological malignancies during CAR-T cell therapy have been reviewed herein, along with recent advancements being made to surmount them.